MENINGKATKAN PARTISIPASI PESERTA DIDIK MELALUI GAME-BASED LEARNING “KAHOOT” PADA PEMBELAJARAN BAHASA INGGRIS - Sundari, Septi; Prasetiya, Benny (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study is an action research aimed at improving participation and motivation among Grade IV B students at SDN Pegirian II/495 Surabaya in learning English through the use of the game-based learning platform "Kahoot". The research was conducted in two cycles with a focus on continuous improvement based on the evaluation of previous cycles. The first cycle involved lesson planning by developing interactive lesson plans and quizzes using Kahoot, followed by observations of student participation and feedback analysis. The results of the first cycle showed an increase in student participation, albeit with technical challenges that needed to be addressed. The second cycle continued with refining the teaching strategies, including the use of additional features within Kahoot to enhance student engagement. The results of the second cycle demonstrated a significant increase in student participation up to 95% and improvements in quiz scores above the average. Qualitative and quantitative analysis of the data confirmed that the implementation of Kahoot successfully increased student motivation through interactive and competitive learning. The implications of this research support the use of game-based learning as an effective approach to enhance English language learning in primary schools, with specific attention to technology adaptation and continuous improvement in the learning process.